SOCIAL FORESTRY DEVELOPMENT STRATEGY IN TUMBANG TARUSAN VILLAGE OF CENTRAL KALIMANTAN - Agusthe, Beben; Ludang, Yetrie; Herianto; Murhaini, Suriansyah; Misrita; Wahyudi (Acta Scientiae et Intellectus, 2024)
One of the social forestry programs implemented by the Indonesian government is village forest. Forest management in Tumbang Tarusan village is currently managed by the assistance of social forestry facilitators from forestry extension agents at the Forestry Service of Central Kalimantan Province. The existence of the Tumbang Tarusan Village Forest is strongly supported by the village government of Tumbang Tarusan as evidenced by the allocation of village funds. In 2019, the Tumbang Tarusan Village Forest Management Institute received honey bee cultivation assistance from the Kalimantan Regional Kalimantan Social and Environmental Forestry Service, but its implementation has now been restructured with a new strategy, which is described descriptively in this paper.